Lithuanian Dramaturgy and Its “Crises” - Klišienė, Neringa (Literatūra, 2021)
The cultural shift that has been taking place over the thirty years since Lithuania regained its independence is bound up with the role of a rapidly changing – in terms of both stage and text – theatre. These changes were mostly expressed through rhetorical formulations of a discourse of “crisis”. It is no exception that this word has been used as a usual descriptor of the state of Lithuanian dramaturgy. Through a discussion of the differing aspects of the relationships between the defenders of the logos theatre and the proponents of stage praxis, this article argues that during the transitionary period that changed Lithuania’s history, and which also supplied the concept of “crisis”, the world of Lithuanian theatre, afflicted with constant perturbations, revealed itself. The multifariousness of “crisis” is also elucidated: at the start of the period of independence the term was used to describe the vacuum problem of Lithuanian drama, after ten years – the lack of current relevant plays, today – the limited access to contemporary dramaturgical texts. The conclusion is thereby drawn, that the dissemination of dramatic texts is not only a prerequisite of lessening the long-lived tensions between text and stage authors, but also of deeper studies of the development of contemporary Lithuanian dramaturgy.
Keywords: Lithuanian dramaturgy; theater; crisis; playwright; stage director